Bacterial Recruitment to Carnivorous Pitcher Plant Communities: Identifying Sources Influencing Plant Microbiome Composition and Function - Grothjan, Jacob J.; Young, Erica B. (Frontiers in Microbiology, 2022)
Processes influencing recruitment of diverse bacteria to plant microbiomes remain poorly understood. In the carnivorous pitcher plant Sarracenia purpurea model system, individual pitchers open to collect rainwater, invertebrates and a diverse microbial community, and this detrital food web is sustained by captured insect prey. This study examined how potential sources of bacteria affect the development of the bacterial community within pitchers, how the host plant tissue affects community development and how established versus assembling communities differ. In a controlled greenhouse experiment, 7 replicate pitchers were allocated to 5 treatments to exclude specific bacterial sources or host tissue: milliQ only, milliQ+insect prey, rainwater+prey, established communities+prey, artificial pitchers with milliQ+prey. Community composition and functions were examined over 8 – 40 weeks using bacterial gene sequencing and functional predictions, measurements of cell abundance, hydrolytic enzyme activity and nutrient transformations. Distinct community composition and functional differences between artificial and real pitchers confirm an important influence of host plant tissue on community development, but also suggest this could be partially related to host nutrient uptake. Significant recruitment of bacteria to pitchers from air was evident from many taxa common to all treatments, overlap in composition between milliQ, milliQ+prey and rainwater+prey treatments, and few taxa unique to milliQ only pitchers. Community functions measured as hydrolytic enzyme (chitinase, protease) activity suggested a strong influence of insect prey additions and were linked to rapid transformation of insect nutrients into dissolved and inorganic sources. Bacterial taxa found in 6 of 7 replicate pitchers within treatments, the ‘core microbiome’ showed tighter successional trajectories over 8 weeks than all taxa. Established pitcher community composition was more stable over 8 weeks, suggesting a diversity-stability relationship and effect of microinvertebrates on bacteria. This study broadly demonstrates that bacterial composition in host pitcher plants is related to both stochastic and specific bacterial recruitment and host plants influence microbial selection and support microbiomes through capture of insect prey.